Transformasi Kebijakan Ekonomi Berdasarkan Ijtima Komisi Fatwa Mui Se-Indonesia VIII : Solusi Menuju Kemandirian Ekonomi Nasional - Zaenol Hasan (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
This study analyses the transformation of economic policy based on the results of the 8th Ijtima Ulama of the Indonesian Fatwa Commission which aims to achieve national economic independence. This policy focuses on strengthening the use of domestic products, empowering UMKM, protecting the national workforce and strengthening the Sharia Economy. A qualitative approach was used to explore the views of economic experts regarding the implementation of the policy. The results show that the use of domestic products, empowerment of UMKM, and protection of national labour are strategic steps to reduce economic inequality and improve people's welfare. This study underlines the importance of synergy between the government, businesses and the community in creating a fairer and more inclusive economic system, based on sharia principles, to achieve sustainable economic independence. The findings provide concrete recommendations for the development of more effective and equitable economic policies.